DETAILED CLINICAL PHENOTYPING OF OXALATE MACULOPATHY IN PRIMARY HYPEROXALURIA TYPE 1 AND REVIEW OF THE LITERATURE. Issue 11 (November 2016) - Derveaux, Thierry; Delbeke, Patricia; Walraedt, Sophie; Raes, Ann; Van Laecke, Steven; Leroy, Bart P.; De Zaeytijd, Julie
Abstract : Purpose: To describe the structural and functional characteristics of oxalate retinopathy. Methods: Five patients with molecularly confirmed primary hyperoxaluria (PH) Type 1 underwent multimodal retinal imaging (spectral-domain optical coherence tomography, white light, and HRA multispectral imaging) and functional testing, including color vision testing, Goldmann perimetry, and International Society for Clinical Electrophysiology of Vision standard electrophysiological testing. Results: Four distinct retinal phenotypes are presented. One patient with a c.[33dupC]; c.[731T>C] mutation showed bilateral perifoveal retinal pigment epithelium hyperplasia. The fundus in the four other patients, all of whom share an identical homozygous c.[33dupC] mutation, ranged from normal to bilateral widespread distribution of retinal crystals and confluent macular retinal pigment epithelium hyperplasia with subfoveal fibrosis. All patients who had developed end-stage renal disease showed some sign of retinopathy, more severe with earlier onset. Conclusion: Retinopathy in PH Type 1 shows considerable interindividual variation. No correlation between genotype and retinal phenotype was detected. Oxalate crystals at the level of the retinal pigment epithelium seem to be irreversible. A proposed clinical grading system of oxalate maculopathy, based on a literature review, may provide clinicians with a tool to better predict visual function and prognosis. Abstract : Supplemental Digital Content is Available in the Text.Four distinct retinal phenotypes in the autosomal recessive disease primary hyperoxaluria Type 1 are presented, and current evidence on the course of retinal disease is reviewed. A proposed clinical grading system of oxalate maculopathy may aid ophthalmologists in clinical estimations of visual function and prognosis.